To question of departure of Nicholas II and royal family to England after fall of monarchy in Russia - M. A. Knyazev (Омский научный вестник: Серия "Общество. История. Современность")
The discussion about the possibility of the departure of Nicholas II and the royal family to England after the February Revolution has been going on for a hundred years, but a definite answer to this question has not yet been worked out in the scientific community. Various researchers among the reasons for the imperial family not to leave for England most often single out the opposition of the Provisional Government, the Petrograd Soviet of Workers ‘and Soldiers’ Deputies, or the Government of England. The author proposes a solution to this issue by critically analyzing the sources of the topic, in particular, the “note” of Nicholas II to the Provisional Government asking him to leave for England. The article uses data from diaries, memoirs, correspondence, as well as paperwork. The conclusion is drawn about the decisive role of the Provisional Government in the Romanovs refusal to leave for the UK